Tripeptides derived from reactive centre loop of potato type II protease inhibitors preferentially inhibit midgut proteases of Helicoverpa armigera - Saikhedkar, Nidhi S.; Joshi, Rakesh S.; Bhoite, Ashwini S.; Mohandasan, Radhika; Yadav, Amit Kumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2018)
Potato type II protease inhibitors (Pin-II PIs) impede the growth of lepidopteran insects by inhibiting serine protease-like enzymes in the larval gut. The three amino acid reactive centre loop (RCL) of these proteinaceous inhibitors is crucial for protease binding and is conserved across the Pin-II family. However, the molecular mechanism and inhibitory potential of the RCL tripeptides in isolation of the native protein has remained elusive. In this study, six peptides corresponding to the RCLs of the predominant Pin-II PIs were identified, synthesized and evaluated for in vitro and in vivo inhibitory activity against serine proteases of the polyphagous insect, Helicoverpa armigera. RCL peptides with sequences PRN, PRY and TRE were found to be potent inhibitors that adversely affected the growth and development of H. armigera. The binding mechanism and differential affinity of the RCL peptides with serine proteases was delineated by crystal structures of complexes of the RCL peptides with trypsin. Residues P1 and P2 of the inhibitors play a crucial role in the interaction and specificity of these inhibitors. Important features of RCL peptides like higher inhibition of insect proteases, enhanced efficacy at alkaline gut pH, longer retention and high stability in insect gut make them suitable molecules for the development of sustainable pest management strategies for crop protection.
Keywords: Helicoverpa armigera; Protease; protease inhibitor; Reactive centre loop peptides

PINIR: a comprehensive information resource for Pin-II type protease inhibitors - Yadav, Nikhilesh K.; Saikhedkar, Nidhi S.; Giri, Ashok P. (BMC Plant Biology, 2021)
Background: Serine protease inhibitors belonging to the Potato type-II Inhibitor family Protease Inhibitors (Pin-II type PIs) are essential plant defense molecules. They are characterized by multiple inhibitory repeat domains, conserved disulfide bond pattern, and a tripeptide reactive center loop. These features of Pin-II type PIs make them potential molecules for protein engineering and designing inhibitors for agricultural and therapeutic applications. However, the diversity in these PIs remains unexplored due to the lack of annotated protein sequences and their functional attributes in the available databases. Results: We have developed a database, PINIR (Pin-II type PIs Information Resource), by systematic collection and manual annotation of 415 Pin-II type PI protein sequences. For each PI, the number and position for signature sequences are specified: 695 domains, 75 linkers, 63 reactive center loops, and 10 disulfide bond patterns are identified and mapped. Database analysis revealed novel subcategories of PIs, species-correlated occurrence of inhibitory domains, reactive center loops, and disulfide bond patterns. By analyzing linker regions, we predict that alternative processing at linker regions could generate PI variants in the Solanaceae family. Conclusion: PINIR (https://pinir.ncl.res.in) provides a web interface for browsing and analyzing the protein sequences of Pin-II type PIs. Information about signature sequences, spatio-temporal expression, biochemical properties, gene sequences, and literature references are provided. Analysis of PINIR depicts conserved species-specific features of Pin-II type PI protein sequences. Diversity in the sequence of inhibitory domains and reactive loops directs potential applications to engineer Pin-II type PIs. The PINIR database will serve as a comprehensive information resource for further research into Pin-II type PIs.
Keywords: annotation; Data analysis; Database; Knowledge representation; Pin-II type protease inhibitor; Protein sequence analysis